Molecular weight and protein binding affinity of leucaena condensed tannins and their effects on in vitro fermentation parameters - Huang, X.D.; Liang, J.B.; Tan, H.Y.; Yahya, R.; Khamseekhiew, B.; Ho, Y.W. (2010)
The objectives of the current study were, firstly to determine the molecular weight of condensed tannins (CTs) of 62-2-8 Leucaena-hybrid Bahru (LLB) and relating it to its protein binding ability, using the local Leucaena leucocephala (LLL) as control and; secondly to evaluate the effect of different levels of CTs of the hybrid LLB on rumen fermentation parameters, including dry matter and nitrogen digestibility and methane gas production. The weight-average molecular weights (M w) of purified CTs extracted from hybrid LLB and local LLL, determined using gel permeation chromatography were near similar, being 2737 and 2872Da, respectively. However, the CTs of the hybrid LLB exhibited stronger protein binding ability than the local LLL (0.305 and 0.420mg, respectively, for LLB and LLL to bind half maximum bovine serum albumin). The above results seems to suggest that molecular mass of CTs, at least for Leucaena forages, is not the sole factor in determining their capability to bind protein. Inclusion of about 20-40mg of CT/g DM of the CTs from hybrid LLB effectively decreased (P<0.05) methane production and in vitro nitrogen digestibility. The above results suggested a potential of using CTs from the hybrid LLB to protect dietary protein from rumen degradation for better utilization in the small intestine of ruminant animals, and in addition to mitigate their enteric methane emission, often implicated as a source of greenhouse gases.